(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Investment is common to all human societies, regardless of whether investment practices contrasts from each another. Indian Post Office Savings Bank being the biggest reserve funds establishments in the nation assume an essential job in mobilising investment funds particularly of the nation and offer various advantages to the financial specialists. Postal Investment Funds frameworks to give contributors who don’t approach banks a protected, helpful technique to set aside cash and to advance sparing among poor people. Investment culture to attitudes, satisfaction, and preference of people, in setting their reserve funds in different money related resources, all the more famously known as investment or Postal Savings. Recurring Deposits, Post Office Saving Bank and Post Office Monthly Income Schemes are the fundamental instruments for investment.